A war on people: drug user politics and a new ethics of community - Zigon, Jarrett (University of California Press, 2019)
"A War on People takes up two interrelated concerns increasingly of import to political anthropologists and theorists. The first is the seemingly widespread lack of motivation for participating in political activity. The second is the political and intellectual focus on critique rather than offering alternatives for possible futures. This book addresses these concerns by offering an ethnographically and theoretically rich look at the political and ethical activity of some unlikely political actors - active and former users of heroin and crack cocaine. Despite this unlikelihood, however, this book shows and argues that the globally-networked anti-drug war movement organized and run by drug users is, in fact, at the forefront of offering an alternative political and social imaginary. In particular, the book focuses on how this anti-drug war imaginary and political activity is enacting non-normative, open, and relationally-inclusive alternatives to such key ethical-political concepts as community, freedom and care. Ultimately, A War on People argues that in a contemporary condition increasingly characterized by widely-diffused complexity and war as governance, an anthropology of potentiality is needed to discern and creatively conceptualize the emerging not-yet of the worlds we research and inhabit"--Provided by publisher